The Effect of Family Literacy Culture on Student’s Motivation in Islamic Education Subject at State Senior High School in Garut - Hilda Ainissyifa; Riska Amelia (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2018)
The environment is believed to have a strong effect on the learning process of students, including the family’s influence. This study is aimed to examine the influence of family literacy culture on student learning motivation in Islamic education subject. This study applied the associative method with inferential statistical analysis. The population of this study covers 484 students of class X at State Senior High School in Garut District, Indonesia, while the number of research samples comprises 83 respondents. Data measurement in this research uses ordinal data with Likert Scale measurement. The analysis methods include regression analysis, correlation coefficient, the coefficient of determination, and hypothesis testing. The results showed that the culture of family literacy had a positive and significant impact on students’ learning motivation in the Subject of Islamic Education